Association of usual walking with mortality in oldest old adults aged 85 years and older: a nationwide senior cohort study. (3rd October 2022) - Jin, M; Yang, P; Yu, H; Kim, T; Lee, H; Pak, H; Lee, M; Joung, B
Abstract: Background: Current guidelines recommend moderate to vigorous intensity physical activity (MVPA) for health benefit in adults. However, it is difficult to meet the recommended minimum MVPA in "oldest old" aged over 85. Although walking is simple and easy exercise for oldest old, research on the association between walking and mortality in oldest old are lacking. Purpose: To investigate the association between walking and the risk of all-cause and cardiovascular mortality among older adults aged 85 years and older. Methods: 7047 participants aged 85 or older underwent the Korean National Health Screening Program, including self-administered questionnaire for physical activity. Reported frequency per week of walking for at least 30 minutes increment was used to classify hours of walking per week. We computed multivariable-adjusted hazard ratios for walking and mutually adjusted for MVPA in relation to all-cause and cardiovascular mortality. Results: The proportions of participants who engaged in walking, moderate- and vigorous-intensity physical activity were 42.5% (2996/7047), 14.7% (1037/7047) and 11.0% (773/7047), respectively. Only 7.6% (538/7047) of participants met the guidelines recommended minimum MVPA. Compared to inactive individuals, those who walked at least 1 hour per week had lower all-cause (HR 0.60 [95% CI, 0.50–0.74]) and cardiovascular mortality risk (HR 0.61 [95% CI, 0.42–0.89]). Walking 1 hour per week was still significant associated with reduction of risk for all-cause (HR 0.50 [95% CI, 0.40–0.61]) and cardiovascular mortality (HR 0.46 [95% CI, 0.30–0.70]) among participants who reported only walking without any MVPA. Conclusions: 1 hour a week of walking might be of benefit for all-cause and cardiovascular mortality in aged over 85 years, even without MVPA. Promoting walking may be a way to help oldest old avoid inactivity and encourage an active lifestyle for all-cause and cardiovascular mortality risk reduction. Funding Acknowledgement: Type of funding sources: None.